PENGARUH SUHU DAN WAKTU PENGERINGAN TERHADAP AKTIVITAS ANTIOKSIDAN DAN SIFAT SENSORIS TEH HERBAL CELUP DAUN RAMBUSA (Passiflora foetida L.) - Nadia Nathaniel, Anabella; Kencana Putra, I Nengah; Sri Wiadnyani, AA. (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 3 (2020): Jurnal ITEPADO - 10.24843/itepa.2020.v09.i03.p07, 2020)
This research aimed to determine the effect of drying temperature and time on antioxidant activity and sensory properties of herbal tea bag of rambusa leaf and to obtain the optimum temperature and drying time that can produce rambusa leaf herbal tea bag with the highest antioxidant activity and the best sensory properties. This research used a completely randomized factorial design with two treatments namely, drying temperature (40°C, 50°C, 60°C) and drying time (3 hours, 3.5 hours, 4 hours). There were 9 factorial combinations, each combination was repeated 2 times. The data obtained were analyzed by analysis of variance. If the treatment had a significant effect, it would be followed by the Duncan test. The results showed that the drying temperature and time treatment had a significant effect (P<0.05) on antioxidant activity, total phenols, total flavonoids, total tannins, water content, color (scoring test), and taste (scoring test), but no significant effect (P>0.05) on the extract content in water, color (hedonic test), taste (hedonic test), and overall acceptance. The results showed that drying temperature of 60°C with a drying time of 3 hours had an optimum drying temperature and time to produce herbal tea bag of rambusa leaf with antioxidant activity of 46.28%, total phenol level of 4.14 mg GAE/g, total flavonoids content of 26.48 mg QE/g, total tannin content of 6.23 mg TAE/g, water content of 8.38%, extract content in water of 31.96%, and sensory properties of yellow color and slight liked, bitter slightly taste and slight liked, and overall acceptance neutral.